Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

For the equation −2 + 3 = 6 a. Find y when x is 3b. Find x when y is 4

Sagot :

Given equation,

[tex]-2x+3y=6[/tex]

(a) Find y when x is 3.

[tex]\begin{gathered} -2\times(3)+3y=6 \\ -6+3y=6 \\ 3y=12 \\ y=4 \end{gathered}[/tex]

(b) Find x when y is 4.

[tex]\begin{gathered} -2x+3y=6 \\ -2x+3\times4=6 \\ -2x+12=6 \\ -2x=-6 \end{gathered}[/tex]

Thus, the value of x is

[tex]\begin{gathered} 2x=6 \\ x=3 \end{gathered}[/tex]